2007
DOI: 10.1007/s10508-007-9220-1
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Early Overt and Covert Sexual Behaviors in Heterosexual Women

Abstract: We used data provided by 417 Kinsey-0 and Kinsey-1 heterosexual women using an anonymous computerized survey to determine the adult correlates of two female-female behaviors that occurred before age 18; 25.4% of participants reported engaging in one or both behaviors. Sexual experimentation with females and masturbating using images of females before age 18 were statistically significant predictors of four different female-female behaviors in adulthood: sexual contact with females, masturbating using images of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 33 publications
3
17
0
Order By: Relevance
“…Striepe and Tolman's (2003) interviews with adolescents also revealed purposeful examinations of heterosexuality as a result of not conforming to prescribed heterosexual gender ideologies for both girls and boys. Several studies have also revealed that a significant subgroup of heterosexual men and women have histories of same-sex attraction and behavior beginning adolescence and continuing into adulthood (Bickham et al 2007;Dunne et al 2000;Kinnish et al 2005;Vrangalova and Savin-Williams 2010). This body of research provides support for the possibility that a heterosexual identity does not consistently reflect stable or uniform heterosexual attraction, fantasy, or behavior.…”
Section: Heterosexual Identity Developmentmentioning
confidence: 93%
“…Striepe and Tolman's (2003) interviews with adolescents also revealed purposeful examinations of heterosexuality as a result of not conforming to prescribed heterosexual gender ideologies for both girls and boys. Several studies have also revealed that a significant subgroup of heterosexual men and women have histories of same-sex attraction and behavior beginning adolescence and continuing into adulthood (Bickham et al 2007;Dunne et al 2000;Kinnish et al 2005;Vrangalova and Savin-Williams 2010). This body of research provides support for the possibility that a heterosexual identity does not consistently reflect stable or uniform heterosexual attraction, fantasy, or behavior.…”
Section: Heterosexual Identity Developmentmentioning
confidence: 93%
“…There is growing evidence that all types of incest that start early in the victims' lives tend to result in early hyper-eroticization of the victims that persists into adulthood (e.g., Beard et al, 2013;Stroebel et al, 2012;Stroebel, O'Keefe, Griffee et al, 2013;Yates, 1982), and the mechanism behind this effect appears to be a type of early learning directly related to sexual functioning called sexual imprinting ; for a review of animal studies on sexual imprinting see Irwin & Price, 1999) working in concert with Pavlovian conditioning and operant conditioning Bickham et al, 2007). Furthermore, sexual imprinting working in concert with Pavlovian conditioning and operant conditioning is the mechanism that explains the powerful tendency of same-sex sibling incest or non-incestuous early experiences with same-sex partners to produce permanent adult same-sex or bisexual orientations in the victims Bickham et al, 2007;Hoffman, 2012;Pfaus et al, 2012;Robinett, 2012;Stroebel, O'Keefe, Griffee et al, 2013).…”
mentioning
confidence: 99%
“…Furthermore, sexual imprinting working in concert with Pavlovian conditioning and operant conditioning is the mechanism that explains the powerful tendency of same-sex sibling incest or non-incestuous early experiences with same-sex partners to produce permanent adult same-sex or bisexual orientations in the victims Bickham et al, 2007;Hoffman, 2012;Pfaus et al, 2012;Robinett, 2012;Stroebel, O'Keefe, Griffee et al, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(2002) found that adults born to older parents were more attracted to partners with older faces than those born to younger parents. Finally, Bickham et al (2007) compared heterosexual women (who were behaviorally Kinsey 0's or 1's) and found that experimenting sexually with females and masturbating using images of females prior to the age of 18 predicted sex contact with females, masturbating to images of females, fantasizing about a female sex partner when having sex with male, and voyeurism directed at women in adulthood. They proposed that because Kinsey 1's have a primarily heterosexual orientation and because analogous early female-male behaviors were not significant predictors of adult female-female behavior (i.e., such behavior did not differ between the Kinsey 0's and 1's) argue against the effect being due to a same-sex predisposition.…”
Section: Nonhumansmentioning
confidence: 99%